A scoping review of research on well‐being across diverse family structures: Rethinking approaches for understanding contemporary families. Issue 4 (13th October 2021) - Jensen, Todd M.; Sanner, Caroline
Abstract: In the United States and across the globe, demographic trends have coalesced to produce an increasingly diverse set of family structures, fueling international interest in exploring diverse family structures as key developmental contexts for adults and children. Given the persistence of research focused on well‐being differences across family structures, and in order to move this research into the future productively, it is critical to rigorously chart and evaluate how this research is being conducted. In this scoping review, we evaluate 283 studies that examined associations between family structure and well‐being. We reflect on dominant methodological trends across four primary domains: (a) approaches to measuring family structure, (b) approaches to analyzing associations between family structure and well‐being, (c) the application of theory, and (d) conceptualizations of well‐being. In evaluating observable trends, we offer recommendations for rethinking where we can (and perhaps should) go next to better understand and support contemporary families.